2006
DOI: 10.1161/01.res.0000204724.29685.db
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated TRPC1 Channel in Vascular Injury In Vivo and Its Role in Human Neointimal Hyperplasia

Abstract: Occlusive vascular disease is a widespread abnormality leading to lethal or debilitating outcomes such as myocardial infarction and stroke. It is part of atherosclerosis and is evoked by clinical procedures including angioplasty and grafting of saphenous vein in bypass surgery. A causative factor is the switch in smooth muscle cells to an invasive and proliferative mode, leading to neointimal hyperplasia. Here we reveal the importance to this process of TRPC1, a homolog of Drosophila transient receptor potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
162
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(171 citation statements)
references
References 31 publications
7
162
1
1
Order By: Relevance
“…In the same study, balloon dilatation of human internal mammary artery showed a similar increase in TRPC1 and TRPC6 mRNA expression 48 h post injury [14]. TRPC1 is upregulated following experimental vascular injury in mice and pigs, and is associated with the conversion of smooth muscle cells from a quiescent to a proliferative phenotype initiating neointimal formation [74]. Upregulation of TRPC1 was associated with enhanced Ca 2+ entry and cell cycle activity.…”
Section: Increased Expression Of Trpc Cation Channelsmentioning
confidence: 70%
See 2 more Smart Citations
“…In the same study, balloon dilatation of human internal mammary artery showed a similar increase in TRPC1 and TRPC6 mRNA expression 48 h post injury [14]. TRPC1 is upregulated following experimental vascular injury in mice and pigs, and is associated with the conversion of smooth muscle cells from a quiescent to a proliferative phenotype initiating neointimal formation [74]. Upregulation of TRPC1 was associated with enhanced Ca 2+ entry and cell cycle activity.…”
Section: Increased Expression Of Trpc Cation Channelsmentioning
confidence: 70%
“…Most studies of VSMC phenotypic switching have focused on identification of factors that promote this process (e.g., growths factors and cytokines, oxidative stress, mechanical stress, endothelial factors) or on transcriptional regulation of phenotype-specific genes [70,101,102]. These studies have mainly focused on the loss of contractile proteins with very few reports devoted to the acquisition of proproliferative or pro-migratory proteins such as ion channels and pumps [14,32,74].…”
Section: Smooth Muscle Phenotypic Switchingmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings show that these waves: (1) are due to regenerative CICR by the receptors for IP 3 (IP 3 R), (2) have a marked latency period, (3) are characterized by a transient increase in SR Ca 2+ ([Ca 2+ ] SR ) both at the point of origin and at the wave front, (4) proceed with diminishing velocity, and (5) are arrested by the nuclear envelope. Our quantitative model indicates that the gradual decrease in the velocity of the SR depletion wave, in the absence of external Ca 2+ , results from continuity of the SR luminal network.In VSMCs, Ca 2+ controls multiple functions, including contraction-relaxation, proliferation, migration and apoptosis, in health and disease [5][6][7]. This could be explained by the widely held view that functional selectivity of the Ca 2+ signal is encoded in its spatial and temporal characteristics [8][9][10].…”
mentioning
confidence: 99%
“…In VSMCs, Ca 2+ controls multiple functions, including contraction-relaxation, proliferation, migration and apoptosis, in health and disease [5][6][7]. This could be explained by the widely held view that functional selectivity of the Ca 2+ signal is encoded in its spatial and temporal characteristics [8][9][10].…”
mentioning
confidence: 99%